ANALISIS PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN HULU SUNGAI UTARA - Kartika, Dewi; Rachman, Abdul; Hendra, Surya; Ritawaty, Noor (KINDAI, 2023)
This research aims to analyze the influence of Work Discipline, Work Environment and Work Motivation partially and simultaneously on Employee Performance at the North Hulu Sungai Regency Education Service. This research was conducted to explain the variables that will be studied and to see the influence of the Work Discipline (X1), Work Environment (X2), and Work Motivation (X3) variables on the Employee Performance variable (Y). The location of this research is the North Hulu Sungai District Education Office. Using saturated sampling, the sample size was 43 samples. The data collection method used was a questionnaire. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The research results show 1) that simultaneously (together), Work Discipline, Work Environment and Work Motivation have a significant effect on Employee Performance at the North Hulu Sungai Regency Education Service. Likewise individually (partially), 2) Work Discipline has a significant effect on Employee Performance, 3) The work environment has a significant effect on employee performance, and 4) Work Motivation has a significant effect on Employee Performance at the North Hulu Sungai Regency Education Office. Keywords: Discipline , Environment, Work Motivation, Performance